Effects of a proprietary mixture of extracts from Sabal serrulata fruits and Urtica dioica roots (WS® 1541) on prostate hyperplasia and inflammation in rats and human cells - Sens-Albert, Carla; Weisenburger, Sabrina; König, Beatrix C.; Melcher, Silas F.; Scheyhing, Ulrike A. M.; Rollet, Karin; Lluel, Philippe; Koch, Egon; Lehner, Martin D.; Michel, Martin C. (Frontiers in Pharmacology, 2024)
Introduction Phytotherapeutics, particularly extracts from Sabal serrulata (saw palmetto) fruit or Urtica dioica (stinging nettle) root, are popular for the treatment of male lower urinary symptoms in many countries, but their mechanism of action is poorly understood. We performed in vivo and in vitro studies to obtain deeper insight into the mechanism of action of WS® 1541, a proprietary combination of a Sabal serrulata fruit and an Urtica dioica root extract (WS® 1473 and WS® 1031, respectively) and its components. Methods We used the sulpiride model of benign prostatic hyperplasia in rats and tested three doses of WS® 1541 in comparison to finasteride, evaluating weight of prostate and its individual lobes as well as aspects of inflammation, oxidative stress, growth and hyperplasia. In human BPH-1 cells, we studied the effect of WS® 1473, WS® 1031, WS® 1541 and finasteride on apoptosis, cell cycle progression and migrative capacity of the cells. Results WS® 1541 did not reduce prostate size in sulpiride treated rats but attenuated the sulpiride-induced changes in expression of most analyzed genes and of oxidized proteins and abrogated the epithelial thickening. In vitro, WS® 1473 and WS® 1031 showed distinct profiles of favorable effects in BPH-1 cells including anti-oxidative, anti-proliferative and pro-apoptotic effects, as well as inhibiting epithelial-mesenchymal-transition. Conclusions This data supports a beneficial effect of the clinically used WS® 1541 for the treatment of lower urinary tract symptoms associated with mild to moderate benign prostate syndrome and provides a scientific rationale for the combination of its components WS® 1473 and WS® 1031.